2015
DOI: 10.1186/s12883-015-0412-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of late-onset Pompe disease in the Middle East and North Africa region: consensus recommendations from an expert group

Abstract: BackgroundPompe disease is a rare autosomal recessive disorder caused by a deficiency of the lysosomal enzyme alpha-glucosidase responsible for degrading glycogen. Late-onset Pompe disease has a complex multisystem phenotype characterized by a range of symptoms.MethodsAn expert panel from the Middle East and North Africa (MENA) region met to create consensus-based guidelines for the diagnosis and treatment of late-onset Pompe disease for the MENA region, where the relative prevalence of Pompe disease is though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 92 publications
2
46
0
5
Order By: Relevance
“…All patients received alglucosidase alfa enzyme replacement therapy (ERT) at the approved dose of 20 mg/kg every 2 weeks, according to consensus recommendations from the Middle East and North Africa (MENA) expert group, after confirmation of LOPD. Patient 7 was noncompliant with BiPAP and ERT, his condition deteriorated, and he died within 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…All patients received alglucosidase alfa enzyme replacement therapy (ERT) at the approved dose of 20 mg/kg every 2 weeks, according to consensus recommendations from the Middle East and North Africa (MENA) expert group, after confirmation of LOPD. Patient 7 was noncompliant with BiPAP and ERT, his condition deteriorated, and he died within 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…Although no previously published guidelines suggest that pre‐symptomatic patients should be treated, some indicate that treatment can be considered in pre‐symptomatic patients with abnormal muscle imaging or biopsy results . Although there is currently no evidence to show whether pre‐symptomatic patients benefit from treatment, and it has been shown that they may remain pre‐symptomatic for years , such patients may already be losing muscle mass, which they may not be able to regain.…”
Section: Discussionmentioning
confidence: 99%
“…Several national practices and published recommendations do include some criteria for withdrawing treatment , but none mention the detection of high antibody levels against alglucosidase alfa that counteract the treatment effect as a reason to stop treatment. The effect of antibodies does seem to be much higher in infants than in adults .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systemic review showed that enzyme replacement therapy was associated an increase of 1.4 % FVC after 2 months [17]. Because of such effective treatments, physicians are advised to be informed about various presentation of Pompe disease, especially respiratory insufficiency as an essentially fatal condition [18].…”
Section: Discussionmentioning
confidence: 99%